Comparison Between Doppler-Echocardiography and Uncalibrated Pulse Contour Method for Cardiac Output Measurement: A Multicenter Observational Study*. Issue 7 (July 2016) - Scolletta, Sabino; Franchi, Federico; Romagnoli, Stefano; Carlà, Rossella; Donati, Abele; Fabbri, Lea P.; Forfori, Francesco; Alonso-Iñigo, José M.; Laviola, Silvia; Mangani, Valerio; Maj, Giulia; Martinelli, Giampaolo; et al.
Abstract : Objectives: Echocardiography and pulse contour methods allow, respectively, noninvasive and less invasive cardiac output estimation. The aim of the present study was to compare Doppler echocardiography with the pulse contour method MostCare for cardiac output estimation in a large and nonselected critically ill population. Design: A prospective multicenter observational comparison study. Setting: The study was conducted in 15 European medicosurgical ICUs. Patients: We assessed cardiac output in 400 patients in whom an echocardiographic evaluation was performed as a routine need or for cardiocirculatory assessment. Interventions: None. Measurements and Main Results: One echocardiographic cardiac output measurement was compared with the corresponding MostCare cardiac output value per patient, considering different ICU admission categories and clinical conditions. For statistical analysis, we used Bland-Altman and linear regression analyses. To assess heterogeneity in results of individual centers, Cochran Q, and the I 2 statistics were applied. A total of 400 paired echocardiographic cardiac output and MostCare cardiac output measures were compared. MostCare cardiac output values ranged from 1.95 to 9.90 L/min, and echocardiographic cardiac output ranged from 1.82 to 9.75 L/min. A significant correlation was found between echocardiographic cardiac output and MostCare cardiac output ( r = 0.85; p < 0.0001). Among the different ICUs, the mean bias between echocardiographic cardiac output and MostCare cardiac output ranged from –0.40 to 0.45 L/min, and the percentage error ranged from 13.2% to 47.2%. Overall, the mean bias was –0.03 L/min, with 95% limits of agreement of –1.54 to 1.47 L/min and a relative percentage error of 30.1%. The percentage error was 24% in the sepsis category, 26% in the trauma category, 30% in the surgical category, and 33% in the medical admission category. The final overall percentage error was 27.3% with a 95% CI of 22.2–32.4%. Conclusions: Our results suggest that MostCare could be an alternative to echocardiography to assess cardiac output in ICU patients with a large spectrum of clinical conditions. Abstract : Supplemental Digital Content is available in the text.